Persistent symptoms are associated with long term effects of COVID-19 among children and young people: Results from a systematic review and meta-analysis of controlled studies. - Sanaz Behnood; Fiona Newlands; Lauren O'Mahoney; Mahta Haghighat Ghahfarokhi; Mohammed Z Muhid; Jake Dudley; Terence Stephenson; Shamez N Ladhani; Sophie Bennett; Russell M Viner; Rowan Bhopal; Paige Kolasinska; et al. (PLoS ONE, 2023)
Background Research on the long-term impact on COVID-19 in children and young people (CYP) has been published at pace. We aimed to update and refine an earlier systematic review and meta-analysis to assess the current evidence for Post-COVID-19 Condition in CYP. Methods Studies from the previous systematic review were combined with studies from a systematic search from July 2021 to November 2022 (registration PROSPERO CRD42021233153). Eligible studies included CYP aged ≤19 years with confirmed or probable SARS-CoV-2 infection and symptoms persisting at least 12 weeks. Findings 55 studies (n = 1,139,299 participants) were included. Over two-hundred symptoms were associated with Post COVID-19 Condition. Gastrointestinal problems, headaches, cough and fever were among the most prevalent symptoms with rates of 50.2%, 35.6%, 34.7% and 25.8% respectively. Twenty-one symptoms from 11 studies were suitable for meta-analysis. There were significantly higher pooled estimates of proportions of symptoms for altered / loss of smell or taste, dyspnoea, fatigue, and myalgia in CYP with confirmed SARS-CoV-2 infection. Heterogeneity was high suggesting substantial variation amongst the included studies. Conclusions Many CYP continue to experience symptoms after SARS-CoV-2 infection. Efforts to aid early identification and intervention of those most in need is warranted and the consequences of COVID-19 for CYP call for long-term follow-up.